Plant-based biofuels [version 1; referees: 2 approved] - Elizabeth E. Hood (F1000Research, 2016)
This review is a short synopsis of some of the latest breakthroughs in the areas of lignocellulosic conversion to fuels and utilization of oils for biodiesel. Although four lignocellulosic ethanol factories have opened in the USA and hundreds of biodiesel installations are active worldwide, technological improvements are being discovered that will rapidly evolve the biofuels industry into a new paradigm. These discoveries involve the feedstocks as well as the technologies to process them.